PENGARUH BEBERAPA INDEKS SAHAM GLOBAL DAN KURS DOLAR (USD) TERHADAP INDEKS HARGA SAHAM GABUNGAN DI BURSA EFEK INDONESIA DAN DAMPAKNYA TERHADAP RETURN SAHAM PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI - Zikri, Muhaimin; Derriawan; Salim, Fahruddin (SEKOLAH PASCASARJANA PRESS, 2020)
The purpose of this study was to determine the effect of the Dow Jones Index, the FTSE 100 Index, the Hang Seng Index, the Straits Times Index, and the USD/IDR Exchange Rate on the Indonesia Composite Stock Price Index (IDX Composite) on the Indonesia Stock Exchange and its impact on the Stock Returns of the Goods Industry Sector companies on the Indonesia Stock Exchange. The sample of this study were 60 research data for the period January 2014 to December 2018. The technique of testing and processing data uses multiple regression analysis with the Eviews program. The results showed that the Dow Jones Index partially had a positive effect on the IDX Composite, while the USD/IDR exchange rate had a negative effect on the IDX Composite. The FTSE 100 Index, the Hang Seng Index, and the Straits Times Index proved to have no significant effect on the IDX Composite. But simultaneously, the five elements have a significant effect on the IDX Composite according to the size of each coefficient. The results also showed that the IDX Composite did not have a significant effect on Stock Returns particularly in the Consumer Goods Industry Sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period.